A Note on Masdevallia zahlbruckneri and M. utriculata (Orchidaceae) - Oses Salas, Lizbeth Melissa (2016)
Masdevallia utriculata and M. zahlbruckeri are characterized and illustrated based on living plants from Costa Rica. The species are compared with each other on the basis of their general similar morphology. Their taxonomic status is reviewed.